The Role for Imaging in the Investigation of Isolated Objective Vestibular Weakness. (1st October 2019) - Gigliotti, Deanna; Blakley, Brian; Moore, Paige; Hochman, Jordan
Abstract : Objective: Unilateral vestibular weakness has considerable potential etiologies. One source is a vestibular schwannoma. This article evaluates, in the absence of other symptoms and signs, if unilateral vestibular weakness is an analogue to asymmetric sensorineural hearing loss and serves as an indication for lateral skull base imaging. Study Design: Retrospective chart review. Setting: Academic tertiary center. Subjects and Methods: All patients undergoing caloric assessment between January 1, 2012, and June 30, 2018, were investigated. Patients with unilateral vestibular weakness (a left‐right difference >25% on electronystagmography) were included in the study. A provincial encompassing image library was surveyed for potential adequate imaging (computed tomography internal auditory canal infused, magnetic resonance imaging [MRI] brain, MRI internal auditory canal) of the target population within the preceding 5 years. Presence/absence of vestibular schwannoma on imaging was determined. Results: Of the 3531 electronystagmography reports reviewed during the period, 864 patients were identified with unilateral vestibular weakness. Of these, 542 had sufficient imaging, and 14 vestibular schwannomas were identified. Only 1 individual had a vestibular weakness in isolation, while the remaining 13 patients also suffered from documented sensorineural hearing loss that would have mandated MRI scanning. Conclusion: The results of our study suggest that, in isolation, vestibular weakness is an insufficient indicator for lateral skull base imaging.